On Some Summability Methods for a q-Analogue of an Integral Type Operator Based on Multivariate q-Lagrange Polynomials. (19th May 2022) - Agrawal, Purshottam Narain; Shukla, Rahul; Baxhaku, Behar
Abstract: The present paper considers a q -analogue of an operator defined by Erkuş-Duman et al. ( Calcolo, 45(1):53–67, 2008) involving q -Lagrange polynomials in several variables. The Korovkin type theorems in the settings of deferred weighted A-statistical convergence and the power series method are investigated.